The occurrence of Austrodiplostomum compactum (Lutz, 1928) (Digenea: Diplostomidae) metacercariae in the eyes of loricariid fish (Siluriformes: Osteichthyes: Loricariidae) from Brazil - Zica, E. O. P. [UNESP]; Brandao, H. [UNESP]; Zawadzki, C. H.; Nobile, A. B. [UNESP]; Carvalho, Edmir Daniel [UNESP]; da Silva, R. J. [UNESP] (Cambridge University Press, 2011)
The aim of this study was to report the occurrence of Austrodiplostomum compactum metacercariae in the eyes of 98 specimens of loricariid fish (Hypostomus ancistroides, H. hermanni, H. iheringii, H. margaritifer, H. regani, H. strigaticeps, Hypostomus sp. and Megalancistrus parananus) from the Chavantes reservoir (23 degrees 07`36 '' S and 49 degrees 37`35 '' W) located in the rio Paranapanema, upper Parana river basin, municipality of Ipaussu, São Paulo State, Brazil. Fish were collected from October 2007 to February 2009 using nylon monofilament gill nets and transported to the field laboratory where they were euthanized and the eyes were taken and examined under a stereomicroscope. Hypostomus ancistroides and M. parananus were not infected by this diplostomid. Hypostomus hermanni and H. margaritifer were represented by only one specimen but both had a high intensity of A. compactum metacercarie (27 and 35, respectively). Hypostomus strigaticeps (n = 45) and H. iheringii (n = 28) were the most representative specimens and the prevalence, mean intensity of infection and mean abundance were 24.4%, 10.3 and 2.7, and 64.2%, 13.1 and 8.4, respectively. No correlation was observed between the intensity of infection and the standard length (r = -0.223; P = 0.827) and weight (r = 0.03; P = 0.779) of studied fish. Similarly, linear regression among these variables showed a poor correlation and indicated that the infection by A. compactum metacercariae occurs similarly in small and large fish specimens. A seasonal pattern of infection was not observed. Hypostomus hermanni, H. iheringii, H. margaritifer and H. strigaticeps were new hosts recorded for A. compactum metacercariae. A review of morphometric data of A. compactum metacercariae is presented.